Estudo comparativo por MEV-EDS de biotitas de granitos paleoproterozoicos reduzidos e oxidados, Província Carajás: interpretações petrológicas e metalogenéticas. - PESSÔA, Cesar Augusto Amador (2022)
The oxidized Bannach and Redenção granites, belonging to the Jamon Suite, and the reduced Antônio Vicente, Velho Guilherme and Serra da Queimada granites, inserted in the Velho Guilherme Intrusive Suite, are some of the anorogenic paleoproterozoic granites of the Carajás Province. They are predominantly composed of syenogranites and monzogranites, altered in different intensities, with biotite as the representative mafic phase. Biotites from Bannach granite exhibit Fe/(Fe+Mg) ratios between 0.72 and 0.79 and AlIV content between 2.52 and 2.96, while those from Redenção granite show Fe/(Fe+Mg) ratios varying from 0.62 to 0.66 and AlIV between 2.56 and 2.82, plotting near the pole of the siderophyllite. In reduced granites, the Fe/(Fe+Mg) ratios and the AlIV values of biotites from less evolved rocks and free from mineralization are similar to those obtained in biotites from oxidized granites. On the other hand, in the more evolved, hydrothermalized and Sn-bearing facies, biotites are enriched in Fe, have higher Fe/(Fe+Mg) ratios (ranging between 0.85 and 1.00), AlIV values slightly lower than 2.5 and are distributed close to the annita pole. Biotites from oxidized and reduced sterile granites dominate in the field of primary magmatic biotites, suggesting little or no rebalancing. Biotites from rocks with Sn plot dominantly in the field of reequilibrated biotites, indicating changes at the end or after their crystallization. The low contents of Mg, Ti and the Mg/(Mg+Fe) ratios, as well as the high values of Si, Al and Fe/(Fe+Mg) found in the biotites of mineralized rocks, allowed a good separation between Sn-bearing and sterile rocks, indicating its preliminary use in prospecting for this type of mineralization. Keywords: reduced granite; oxidized granite; biotite; mineralization; Carajás Province.